A laminin-based therapy for dogs with chronic spinal cord injury: promising results of a longitudinal trial - Chize, Carolina de Miranda; Vivas, Diego Gonzales; Menezes, Karla; Freire, Max Nascimento; Jiddu, Rodrigo Ferreira Pinto; Graça-Souza, Aurélio Vicente; de Souza-Leite, Eliel; Louzada, Paulo Roberto; Coelho-Sampaio, Tatiana (Frontiers in Veterinary Science, 2025)
IntroductionPolylaminin, an improved form of the natural protein laminin, has been shown to promote axonal regeneration and functional recovery in animal models of acute spinal cord injury (SCI), and is safe and potentially beneficial in humans when administered within the first days after traumatic SCI. This study aimed to evaluate the effect of polylaminin in dogs with chronic SCI.MethodsWe conducted a prospective, longitudinal study in six paraplegic dogs with severe chronic thoracolumbar SCI (T3-L3) caused by trauma (n = 2) or disc degeneration (n = 4). The study assessed whether gait scores, measured during an extended screening period (at least 4 months), would improve during the follow-up (6 months). Polylaminin was delivered intraspinally at a dose of 1 μg/kg, in combination with either glial-derived neurotrophic factor (GDNF; Group 1; n = 3) or chondroitinase ABC (Group 2; n = 3). Safety was assessed through neurological examinations, blood tests and monitoring of medical complications. Gait analysis was carried out using the Texas Spinal Cord Injury Scale (TSCIS) and the Open Field Scale (OFS), while a linear mixed model was used for statistical analysis. During the screening period, dogs received physiotherapy twice per week and had their gait scored periodically. The first six dogs whose scores had remained stable across three evaluations were enrolled. After owners provided informed consent, dogs were randomly allocated to either treatment group.ResultsNo neurological deterioration, serious clinical events or notable deviations in blood tests were observed. The TSCIS average baseline score increased from 2.2 to 3.2 (95% CI: 0.77–1.2; p < 0.001), while the OFS score increased from 1.5 to 3.1 (95% CI: 1.3–1.9; p < 0.001).DiscussionAlthough the present study could not discriminate between the benefits of the two treatments, our findings suggest that polylaminin, in combination with GDNF or chondroitinase ABC, is a safe and potentially effective treatment, which underscores the relevance of further studies to establish a new approach to improving gait function in dogs with chronic SCI.